Iris indocyanine green videoangiography in diabetic iridopathy. Issue 5 (May 1996) - Parodi, M B; Bondel, E; Russo, D; Ravalico, G
Abstract : AIMS/BACKGROUND: Iris fluorescein angiography (IFA) is not commonly used in clinical practice, although its value has been demonstrated especially in cases of diabetic disease. IFA is able to show neovascular tufts in order to guide the laser treatment, and it is highly recommended in diabetic patients who need cataract surgery or vitrectomy. Nevertheless, IFA fails to demonstrate the iris vascular pattern in heavily pigmented iris and conspicuous leakage cases. The aim of the study was to evaluate the feasibility of iris indocyanine green videoangiography (IICGV) and to correlate its findings with those of IFA in diabetic iridopathy. METHODS: Thirty six patients affected in varying degrees by diabetic retinopathy underwent an ophthalmic examination including retinal fluorescein angiography, IFA, and IICGV. IICGV was performed using IMAGEnet System H1024. RESULTS: The results demonstrated that IICGV allows precise visualisation of the iris vascular pattern, also in cases of heavily pigmented iris. CONCLUSIONS: Three main findings seemed to be evident: firstly, iris neovascularisations are detected with IFA far more easily than IICGV; secondly, capillary dilatations and iris hypoperfusion are identified far more clearly using IICGV; thirdly, there is no evident relation between capillary dilatation or iris hypoperfusion, and degree of diabetic retinopathy.